2005
DOI: 10.1254/jphs.fp0040574
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excretion of Urinary 20-HETE in Rats With Cyclosporine-Induced Nephrotoxicity

Abstract: Abstract. The present study examined the contribution of 8,11, in cyclosporine A (CsA)-induced renal nephrotoxicity. Treatment of rats with CsA (50 mg / kg) for 9 days induced renal damage as indicated by marked increase in urine flow (from 9.0 ± 0.3 ml / day to 46.6 ± 7.1 ml / day) and a 3 -5-fold rise in blood urea nitrogen (BUN) levels. The urinary excretion of 20-HETE increased from 164 ± 5 ng/ day (N = 5) to 2432 ± 290 ng/ day (N = 5, P<0.01) after 9 days of CsA treatment. The increase in the urinary excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The observation in this study that the inhibition of 20-HETE with HET0016 or 1-aminobenzotriazole blunted the proteinuria and increase in blood pressure in rats treated with cyclosporin A supports a major role for 20-HETE in cyclosporin A pathology and an attendant increase in blood pressure. These observations are consistent with the data that cyclosporin A treatment led to increased 20-HETE production [15] and increased AA metabolism to 19-HETE and 20-HETE in the liver, but surprisingly not in the kidney S9 fraction [16]. In the latter study, the effect of cyclosporin A on hepatic CYP450 was dependent on the isoform, dose and duration of cyclosporin A treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observation in this study that the inhibition of 20-HETE with HET0016 or 1-aminobenzotriazole blunted the proteinuria and increase in blood pressure in rats treated with cyclosporin A supports a major role for 20-HETE in cyclosporin A pathology and an attendant increase in blood pressure. These observations are consistent with the data that cyclosporin A treatment led to increased 20-HETE production [15] and increased AA metabolism to 19-HETE and 20-HETE in the liver, but surprisingly not in the kidney S9 fraction [16]. In the latter study, the effect of cyclosporin A on hepatic CYP450 was dependent on the isoform, dose and duration of cyclosporin A treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The metabolites derived via v/v-1 hydroxylase pathways, especially 20-HETE, generally elicit constriction whereas metabolites derived via the epoxygenase pathway generally elicit vasodilation and are one of the candidates for endothelial-derived hyperpolarizing factor [21]. In a recent study [15], 20-HETE production was shown to be increased in rats treated with cyclosporin A. Coincidentally, the side-effects of cyclosporin A when used as an immunosuppressant include afferent arteriolar constriction [1], reduced glomerular filtration rate [2], and hypertension [3,4], effects that are also produced by 20-HETE [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6) In platelets, TXA 2 is produced mainly via COX-1-TXA 2 synthase from AA, which is increased dramatically via the action of phospholipase (PL) C and PLA 2 -mediated phospholipid hydrolysis when platelets are activated by various inducers. [7][8][9][10][11] On the other hand, 12-HETE, a parallel metabolite of AA via 12-LOX, has also been reported to act as a platelet activator promoting thrombus formation in vivo 12,13) and to give rise to platelet aggregation and aortic smooth muscle cell migration in vitro. [14][15][16] It is likely that 12-HETE as well as TXA 2 is involved in the initiation and propagation of thrombotic and atherosclerotic disorders.…”
Section: Jjk694 a Synthesized Obovatol Derivative Inhibits Plateletmentioning
confidence: 99%
“…In platelets, TXA 2 is mainly produced via cyclooxygenase (COX)-TXA 2 synthase from arachidonic acid (AA), which is increased dramatically via action of phospholipase (PL) C and PLA 2 -mediated phospholipid hydrolysis, when platelets are activated by various inducers (5 -9). On the other hand, 12-hydroxy-5,8,10,14-eicosatetraenoic acid (12-HETE), a parallel metabolite of AA via 12-lipoxygenase (12-LOX), has also been reported to act as a platelet activator to promote thrombus formation in vivo (10,11) and gives rise to platelet aggregation and aortic smooth muscle cell migration in vitro (12 -14). It seems likely that 12-HETE as well as TXA 2 is involved in the initiation and propagation of thrombotic and atherosclerotic disorders.…”
Section: Introductionmentioning
confidence: 99%